Respuestas
Respuesta dada por:
1
Respuesta:
8e - 28 = 6e + 22 : e = 25
Explicación paso a paso:
pasos
8e - 28 + 28 = 6e + 22 + 28
simplificar
8e = 6e + 50
restar 6e de ambos lados
8e - 6e = 6e + 50 - 6e
simplificar
2e = 50
dividir ambos lados entre 2
2e/2 = 50/2
simplificar
e= 25
Adjuntos:
![](https://es-static.z-dn.net/files/dc8/3b8c06b55de4a8d8c9425cec2cf55378.png)
![](https://es-static.z-dn.net/files/d7b/3b17ce0db28e8bbcf26f9aed72ecaa34.png)
Preguntas similares
hace 2 años
hace 5 años
hace 5 años
hace 5 años
hace 7 años
pasos
8e - 28 + 28 = 6e + 22 + 28
simplificar
8e = 6e + 50
restar 6e de ambos lados
8e - 6e = 6e + 50 - 6e
simplificar
2e = 50
dividir ambos lados entre 2
2e/2 = 50/2
simplificar
e= 25